2012
DOI: 10.4067/s0034-98872012000800004
|View full text |Cite
|
Sign up to set email alerts
|

Resultados del trasplante renal en portadores de ríñones poliquísticos

Abstract: Background: Patients with autosomal dominant polycystic kidney disease (ADPKD) have a better survival in chronic dialysis (Rev Med Chile 2012; 140: 990-998).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…20 Similarly, Moroni and associates showed that the incidence of acute and chronic rejection was not higher in patients with focal segmental glomerulosclerosis or idiopathic membranous nephropathy than in those with other causes of end-stage renal disease. 21 The same results were obtained by Vega and associates who found no differences in rate of acute rejection episodes between kidney transplant recipients who had polycystic kidney disease and the control group, 22 with this finding also supported by Kute and associates. 23 Regarding recurrence of original kidney disease, our study showed a statistically significant difference in the 4 groups regarding the incidence of recurrence, most commonly occurring with glomerular disorders.…”
Section: Discussionsupporting
confidence: 78%
“…20 Similarly, Moroni and associates showed that the incidence of acute and chronic rejection was not higher in patients with focal segmental glomerulosclerosis or idiopathic membranous nephropathy than in those with other causes of end-stage renal disease. 21 The same results were obtained by Vega and associates who found no differences in rate of acute rejection episodes between kidney transplant recipients who had polycystic kidney disease and the control group, 22 with this finding also supported by Kute and associates. 23 Regarding recurrence of original kidney disease, our study showed a statistically significant difference in the 4 groups regarding the incidence of recurrence, most commonly occurring with glomerular disorders.…”
Section: Discussionsupporting
confidence: 78%